A longitudinal study of ICD-11 PTSD and complex PTSD in the general population of Israel. (April 2020) - Hyland, Philip; Karatzias, Thanos; Shevlin, Mark; Cloitre, Marylène; Ben-Ezra, Menachem
Highlights: 11.6% (T1) and 9.0% (T2) of the general population of Israel met diagnostic requirements for ICD-11 PTSD and Complex PTSD. The prevalence rates of PTSD and Complex PTSD remained stable over the course of one year. DSO symptoms are persistent over time and reinforce and intensify PTSD symptoms. Clinical interventions that specifically address DSO symptoms may be of value. Abstract: The ICD-11 includes two trauma disorders: Posttraumatic Stress Disorder (PTSD) and Complex PTSD (CPTSD). CPTSD is a disorder comprised of PTSD and Disturbance in Self-Organization (DSO) symptoms. Evidence supports the construct validity of PTSD and CPTSD, however, the temporal stability of these constructs has rarely been tested. This study examined the diagnostic stability of PTSD and CPTSD, and the temporal associations between PTSD and DSO symptoms over a period of one-year. Data were collected from a nationally representative sample of Israeli adults ( n = 1, 003) and one year later a random half of this sample were reassessed ( n = 543). There were no statistically significant changes in rates of PTSD (6.7%, 5.3%) and CPTSD (4.9%, 3.7%) over time. Latent variable cross-lagged analysis indicated that PTSD and DSO symptoms were stable over time and that DSO symptoms predicted subsequent PTSD symptoms. Results suggest that ICD-11 PTSD and CPTSD are stable constructs in the general population over a period of one year. We discuss the possibility that these findings are influenced by the specific cultural context of Israel. Additionally, given the stability and influence of DSO symptoms we discuss the potential value of psychological therapies that directly address these symptoms.